2007
DOI: 10.1080/00365590601183055
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of p53, Ki-67, microstaging and microvessel density in pT1G3 bladder tumors: Creation of risk groups for progression

Abstract: Microstaging and p53 positivity have a prognostic value for predicting progression in T1G3 tumors, providing 33% more information than that obtained with classical prognostic factors alone. The application of mathematical models identifies risk groups and allows the use of an early and more aggressive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The PubMed literature review was conducted for objectives 1 and 2 of the current study. The selected 46 original articles included a clear-cut description of the methods used to assess T1 subcategorization (32 histoanatomic [n=2992 patients], 14 semiquantitative [n=3717 patients]) and their clinical significance (n=46) expressed as disease recurrence or disease progression, recurrence-free survival, or progression-free survival, cancer-specific survival, overall survival, or combinations thereof 9–54 . Most studies revealed significant prognostic impact (disease recurrence, n=6 studies; disease progression, n=18 studies; recurrence-free survival, n=6 studies; progression-free survival, n=13 studies; cancer-specific survival, n=7 studies; overall survival, n=3 studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PubMed literature review was conducted for objectives 1 and 2 of the current study. The selected 46 original articles included a clear-cut description of the methods used to assess T1 subcategorization (32 histoanatomic [n=2992 patients], 14 semiquantitative [n=3717 patients]) and their clinical significance (n=46) expressed as disease recurrence or disease progression, recurrence-free survival, or progression-free survival, cancer-specific survival, overall survival, or combinations thereof 9–54 . Most studies revealed significant prognostic impact (disease recurrence, n=6 studies; disease progression, n=18 studies; recurrence-free survival, n=6 studies; progression-free survival, n=13 studies; cancer-specific survival, n=7 studies; overall survival, n=3 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been conducted to identify the prognostic role of lamina propria invasion and to determine the best method to assess T1 subcategorization 9–54 . The 2 main approaches applied for bladder T1 subcategorization are histoanatomic methods using the presence of muscularis mucosae (MM) as a landmark, and (semi)quantitative methods using ocular micrometer or high-power fields–based assessment of extent of invasion 9–54 . Most reported data using tumor invasion above, in, or beyond the MM have demonstrated worse prognosis for T1 tumors invading in or beyond MM when compared with tumors invading above MM 9–11,13–17,19–31,33–43,49,50,53 .…”
mentioning
confidence: 99%
“…For each study, the data were extracted (S2 Table). Five studies were performed in Asia (10)(11)(12)(13)(14), 20 were performed in Europe (2,7,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and 10 were performed in North America (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). RFS was evaluated in 20 studies, PFS was evaluated in 31 studies and CSS was evaluated in 12 studies.…”
Section: Resultsmentioning
confidence: 99%
“…43 p53 can provide 33% more information than that obtained with classical prognostic factors alone, and positivity for p53 has a prognostic value in predicting the progression of pT1 UBC tumors. 44 However, the correlation of p53 expression with stage and grade has been questioned, either alone or in combination with Ki-67. 45 In the present study, a high Ki-67 proliferation index combined with abnormal E-cadherin expression was correlated with worse survival rates compared with tumors with a low proliferation index and normal E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%